Comportement elastoplastique anisotrope pour I’ analyse numerique des coques minces en grandes transformations - Boubakar, M. Lamine; Boisse, Philippe (European Journal of Computational Mechanics, 1998)
Due to rolling and cristallographic texture development, thin sheets metal for stamping exhibit an initial orthotropic plastic behaviour that have to be incorporated in numerical modelling of sheet forming processes. A mechanical modelling of the behaviour is presented. It is based on a formulation in a rotating frame updatted using the proper rotation tensor. The stress calculation algoritlim associated is based on the prediction-correction method in the rotating frame and explicitly takes into account shell kinematics with mixed transverse shear interpolation. Numerical results on deep drawing problems show the accuracy and the efficiency of the proposed approach.